Undervalued potential of crassulacean acid metabolism for current and future agricultural production. (7th June 2019) - Davis, Sarah C; Simpson, June; Gil-Vega, Katia del Carmen; Niechayev, Nicholas A; Tongerlo, Evelien van; Castano, Natalia Hurtado; Dever, Louisa V; Búrquez, Alberto
Abstract : A review of the agricultural value of plants that use crassulacean acid metabolism, spanning traditional knowledge and uses, recent genomic discoveries, physiological adaptations, and known commercial values. Abstract: The potential for crassulacean acid metabolism (CAM) to support resilient crops that meet demands for food, fiber, fuel, and pharmaceutical products far exceeds current production levels. This review provides background on five families of plants that express CAM, including examples of many species within these families that have potential agricultural uses. We summarize traditional uses, current developments, management practices, environmental tolerance ranges, and economic values of CAM species with potential commercial applications. The primary benefit of CAM in agriculture is high water use efficiency that allows for reliable crop yields even in drought conditions. Agave species, for example, grow in arid conditions and have been exploited for agricultural products in North and South America for centuries. Yet, there has been very little investment in agricultural improvement for most useful Agave varieties. Other CAM species that are already traded globally include Ananas comosus (pineapple), Aloe spp., Vanilla spp., and Opuntia spp., but there are far more with agronomic uses that are less well known and not yet developed commercially. Recent advances in technology and genomic resources provide tools to understand and realize the tremendous potential for using CAM crops to produce climate-resilient agricultural commodities in the future.